The Determinants of Sexually Transmitted Infections (STIs) among Female Sex Workers (FSWs) in Indonesia: The Literature Review - Abil Rudi; Yunida Haryanti; Lea Masan; Maretalinia Maretalinia; Aris Yulianto (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2020)
STIs is the 10 biggest serious disease in many developing countries, primarily among FSWs (female sex workers). Additionally, the Ministry of Health Indonesia in January-March 2017 reported Female Sex Worker is the highest risk population (8.765 cases) regarding to syndrome approach and laboratory examination to have STIs with diagnosing outcome. The objective of this study is to conduct a literature review and to examine the determinants of STIs among FSWs as found in the published papers. The subject of this study is female sex workers in Indonesia. This study used literature review from six internet data based (Scopus, Medline, Google Scholar, ProQuest, CINAHL, and PubMed). It got 183 scientific articles and selected 17 based on inclusion criteria. The articles chronicled by inclusion criteria in the revised PRISMA flow diagram of article review and inclusion and review by Social Cognitive Theory (SCT). The selected articles were published between 1997 to 2016. Variables which reviewed consist of: cognitive/personal factors which were found are age (14 of 17), education (7 of 17), duration of sex work (7 of 17), behaviour factors which found condom use (8 of 17), number of client (7 of 17), past symptoms (3 of 17), environmental factors which found sex venue (2 of 17), place of origin (2 of 17), and protection (1 of 17). Strongly determinants related to STIs among FSWs in Indonesia are age, education, duration of sex work, condom use, number of clients, past symptoms, sex venue, place of origin, and protection.